Rancang bangun alat/mesin rol pres cetak label kulit - Asmongin, Asmongin; Supriyadi, Supriyadi (Majalah Kulit, Karet, dan Plastik, 1997)
Design of preparation roll press stamping machine for leather was carried out to produce machine, that can be used for stamping motives on leather grain sides, especially for vegetable tanned leather. This machine can help small industry or home industry to produce leather goods, such as belts, wallets, ladyâs bags and labels. The technical specification of the machine is : the diameter of stamping roll and feeding roll are about 60 mm, the length of the rolls are about 200 mm, roll rotation about 7.4 rpm. The electrical motor is about 0.5 HP ; 1450 RPM; 1 Phase and the cacity of the machine is 1.272 meter / minute. Â Â INTISARIÂ Rancang bangun alat/mesin rol pres cetak label kulit dilaksanakan untuk membuat mesin yang dapat mencetak motif timbul pada kulit, khususnya kulit samak nabati. Alat ini dapat membantu industri kecil/industri rumah tangga yang memproduksi barang-barang kerajinan dari kulit seperti ikat pinggang, dompet, tas wanita, dan merk/label kulit untuk barang-barang kerajinan. Spesifikasi alat ini adalah : diameter rol cetak dan rol pembawa kulit 60 mm dan panjang 200 mm, putaran 7,4 RPM, dijalankan oleh motor listrik 0,5 HP ; 1450 RPM ; 1 Phase. Kapasitas mesin adalah 1,272 meter / menit.